eCM 2011
DOI: 10.22203/ecm.v022a10
|View full text |Cite
|
Sign up to set email alerts
|

The effect of synthetic octacalcium phosphate in a collagen scaffold on the osteogenicity of mesenchymal stem cells

Abstract: Although the effi cacy of the in vivo osteogenic capabilities of synthetic octacalcium phosphate (OCP) crystal implantation can be explained through its stimulatory capacity for the differentiation of the host osteoblastic cell lineage, direct evidence that OCP supports bone regeneration by osteogenic cells in vivo has not been shown. Mesenchymal stem cells (MSCs) isolated from 4-week-old male Wistar rat long bones were pre-incubated in osteogenic or maintenance medium in the presence or absence of basic fi br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…In the control group, the defect was filled with fibrous connective tissue with a few calcified bodies. These results were compatible with previous results, whose rat calvarial defect was implanted with -TCP particle with or without collagen 15) . Thus, our histological analysis also suggests a synergistic effect of TB and collagen on bone regeneration.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the control group, the defect was filled with fibrous connective tissue with a few calcified bodies. These results were compatible with previous results, whose rat calvarial defect was implanted with -TCP particle with or without collagen 15) . Thus, our histological analysis also suggests a synergistic effect of TB and collagen on bone regeneration.…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that the combinatorial application of TB and collagen results in a synergistic effect on bone formation. A similar finding has been reported by using synthetic octacalcium phosphate and collagen 15,18) . Quantitative analysis of 3D micro-CT image revealed that the bone volume was found to be significantly higher in the collagen and combination groups, than in the TB group.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[4][5][6][7][8] From the viewpoint of bone regenerative properties, autologous bone is still the first choice for filling defects due to its superior osteoconductivity, since autologous bone consists of osteoblastic cells, growth factors, such as bone morphogenetic proteins, and matrix materials, including collagen and hydroxyapatite (HA) crystals. Although the tissue-engineering technique by introducing exogenous cells into the OCP-based material certainly increases the osteogenic capability of the material, 9 the use of bone-substitute materials that have biological activity compatible with that of autologous bone, with the stimulation of host osteoblastic cells around OCP crystals, is still preferable from the viewpoint of reducing the complex handling and the cost of the preparation of an implant form. We recently succeeded in synthesizing such material 10 with bone regenerative capability approaching that of autologous bone to repair a critically sized rat calvaria defect composed of an OCP co-precipitated gelatin (Gel) composite obtained through OCP crystal growth in a solution containing Gel molecules.…”
Section: Introductionmentioning
confidence: 99%